The Utilization of Ethanol as Antisolvent to Enhance the Glucomannan Content of Tuber of Amorphophallus muelleri Blume - Rachmaniah, Orchidea; Putri, Hazira Larasati Novida; Maharany, Cindy Shofya; Hendrianie, Nuniek; Juliastuti, Sri Rachmania; Darmawan, Raden; Fahmi, Fahmi; Meka, Wahyu (IPTEK The Journal for Technology and Science, 2025)
Porang (Amorphophallus muelleri Blume) is widely found in Indonesia. The high glucomannan (GM) content in Porang (Amorphophallus muelleri Blume) compared to other tubers becomes the main advantage of Porang. Glucomannan is a low-calorie fibre polysaccharide with a beta-1,4 bond composed of D-glucose and D-mannose. However, its calcium oxalate (CaC2O4) content is an issue and should be minimized when consumed. The research focused on increasing the GM content of raw Porang tuber donated from PT ABS., Bogor. Initially, the raw material was roughly sliced and soaked in sodium chloride (NaCl) solution with concentrations of 10% or 15% weight by weight, washed with gently warm water (approximately 40 degrees Celsius), and air dried to result in crude konjac flour (CKF). Further purification of CKF will produce konjac glucomannan (KGM). The KGM has a higher content of glucomannan. Ethanol (EtOH) was used as an antisolvent in the purification step. The final product of KGM was analyzed regarding GM, calcium oxide, moisture, and ash content. A 15% weight by weight sodium chloride solution followed by warm water washing could reduce the calcium oxalate (CaC2O4) content by 59%. Meanwhile, further purification using 50% ethanol increased glucomannan content by 627.85% from its initial value in Porang tubers. Hence, the treatment combination of sodium chloride–warm water washing and ethanol purification maximally removes calcium oxide and increases the GM content in the KGM.